Changes in Health-related Parameters Associated with Sports Performance Enhancement Drugs - Wiacek, Magdalena; Trąbka, Bartosza; Tomasiuk, Ryszard; Zubrzycki, Igor Z (International Journal of Sports Medicine, 2022)
The purpose of this study was to evaluate changes in health-related parameters caused by the administration of anabolic-androgenic steroids and “fat-burning drugs” during a 6-month competition preparation period. The physiological, biochemical, and anthropometric parameters studied included serum cholesterol, triglycerides, high-density lipoprotein cholesterol, low-density lipoprotein cholesterol, aspartate aminotransferase, alanine transaminase, bilirubin, body mass, and percentage of total body fat. Changes in the parameters studied were analyzed at monthly intervals during six months of preparation for competition. The study revealed a continuous increase in body mass, accompanied by a decrease in body fat percentage to the physiologically essential level. Total cholesterol levels remined in the desirable concentration range. The mean levels of triglycerides fluctuated between borderline high and high. Mean high-density lipoprotein cholesterol levels remained within the low range, while low-density lipoprotein cholesterol fluctuated between near-optimal / above-optimal, borderline high, and high levels. Serum levels of aspartate aminotransferase and alanine transaminase remained within the high concentration. The bilirubin concentration remained in the desirable range. The blood nitrogen urea concentration fluctuated between normal and elevated levels. Sports-enhancing drugs analyzed in this study do not have an immediate detrimental impact on the selected biochemical, physiological, and anthropometric parameters that define health.
Keywords: sport enhancement drugs; professional sports; bodybuilding